Private resources governance to public destination (2019)
This paper studies the problem of private organizations role on governance, in order to advance in the understanding of decision-making processes regarding to the assignment of private resources on public issues. In particular, from an institutionalist perspective and using polycentric governance as an analytical category, it studies the decision of some private organizations to allocate resources on public education in Antioquia, Colombia. The qualitative analysis allows asseverate that, indeed, there are multiple decision-making centers lack in articulation but, at the same time, with formal and informal scenarios to get cooperative agreements. In brief, this paper is a contribution to governance analysis on public issues from a private perspective, an issue that deserves to be more explored from government and public policies studies due to it constitutes an important matter on the public decisions processes.